(untitled) (Vietnam Journal of Community Medicine, 2021)
This cross sectional study looks at all documents, records, in-depth interviews with province and district medical leaders as well as at group discussions with medical staff at Lao Cai General Hospital in order to describe the phenomenon of providing continuing medical education service of Lao Cai General Hospital for the period 2015 - 2019. Result: In 5 years (2015 - 2019), the hospital provided 31 education programs, 137 education courses for 5408 medical officers with the ratios of expertise - management - soft skills were 63.63% - 20.38% - 15.99%; cooperated with other training institutions to provide 65 education courses for 4396 medical officers. The number of trainees decreased gradually every year. Some of the factors affecting service supply are: funds from the State budget; cooperation with other continuing education institutions; not enough attention to continuing education of medical facilities in the area; limited training capacity of the Hospital.